Uma abordagem estocástica baseada em aprendizagem por reforço para modelagem automática e dinâmica de estilos de aprendizagem de estudantes em sistemas adaptativos e inteligentes para educação a distância - Dorça, Fabiano Azevedo (2012)
An important feature in Distance Education is the personal and intelligent assistance, in which an important aspect is that students may have quite different profiles. Thus, a course designed for a particular student may not be suitable for other students. Because of this, a challenge in research is the development of advanced educational applications that provide some degree of intelligence and adaptivity. An indispensable factor in this type of system is the accurate identification of students learning styles, in order to provide most suited content to their individual needs. The construction of this kind of system through a probabilistic process is an important research problem, because these systems need to deal with incomplete or uncertain information about students. Thus, adaptivity provided by these systems need to consider a certain level of uncertainty. So, we strongly believe that considering stochastic student modeling in these systems is essential. Therefore, the main goal of this work is to present an innovative stochastic approach, based on reinforcement learning, for providing adaptivity through probabilistic modeling of students learning styles, and to investigate its efficiency, effectiveness and reliability through a series of experiments. Specifically, the proposed approach aims to detect and correct, automatically and dynamically, inaccuracies and inconsistencies in learning styles stored in the student model, considering that preferences obtained through psychometric questionnaires may need review, by having some degree of uncertainty. In this context, this work discusses and addresses important issues on automatic and dynamic modeling of learning styles, most of them ignored by approaches developed so far.